Elderly patients affected by head and neck squamous cell carcinoma unfit for standard curative treatment: Is de-intensified, hypofractionated radiotherapy a feasible strategy?. (November 2017) - Bonomo, Pierluigi; Desideri, Isacco; Loi, Mauro; Lo Russo, Monica; Olmetto, Emanuela; Maragna, Virginia; Francolini, Giulio; Delli Paoli, Camilla; Grassi, Roberta; Pezzulla, Donato; Greto, Daniela; Meattini, Icro; et al.
Highlights: The treatment of elderly patients with head and neck cancer is challenging. Hypofractionated radiotherapy provides clinical benefit in frail, elderly patients. A PTV larger than 200 cc is an unfavorable prognosticator of response. Abstract: Objectives: The aim of our work was to report on the clinical outcome of a moderately hyprofractionated radiotherapy regimen in elderly patients affected by head and neck squamous cell carcinoma (HNSCC). Material and methods: HNSCC aged ≥65 deemed unsuitable for curatively-intended concurrent chemo-radiotherapy or high-dose radiotherapy by clinical judgement were further evaluated with the Geriatric 8 (G8) questionnaire and Charlson comorbidity index (CCI). In case of a G8 score ≤14, a de-intensified radiation schedule of 40 Gy delivered in 16 fractions was prescribed. Results: Thirty-six patients were treated between 2011 and 2016. The median age of the cohort was 77.5 (range: 65–91 years) with a combined ECOG PS of 2–3 in 77.8% and CCI of ≥8 in 25% patients, respectively. At a median follow-up of 13 months (range 2–62 months), the 6-month and 1-year rates of loco-regional control and progression-free survival were 42%, 28% and 36% and 20%, respectively. At univariate analysis, log-rank test showed that age >75 years (p = 0.036), worse PS (ECOG ≥ 2; p = 0.027), lower G8 score (<9; p = 0.027) and PTV volume greater than 200 cc (p = 0.038) had a significant correlation with PFS. The negative impact of the PTV volume on PFS was the only parameter confirmed in the multivariate analysis (HR 2.68; 95% CI: 1.24–5.81, p = 0.013). No grade 4–5 toxicity was observed, while 13/36 patients (36%) had G3 acute side effects. Conclusion: The hypofractionated radiation schedule evaluated provides clinical benefit with low toxicity in frail, elderly patients affected by locally advanced HNSCC.